Journal of Human Sport and Exercise - 2018 - Spring Conferences of Sports Science 2018
DOI: 10.14198/jhse.2018.13.proc2.06
|View full text |Cite
|
Sign up to set email alerts
|

Differences between students according to physical activity and their motivation, basic psychological needs and responsibility

Abstract: The objective of this research was to analyse the differences in physical activity, basic psychological needs, motivation and responsibility in students. A sample of 109 participants was chosen (M = 16.29, SD = .95), who were given a questionnaire to assess their satisfaction of basic psychological needs (PNSE), motivation (BREQ-2) and responsibility (PSRQ), together with a physical activity measurement instrument. The participants were grouped for analysis according to the percentile of physical activity in "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Results from other studies also highlight significant quantitative variability between weekday and weekend PA among adolescents (Pelclová et al, 2010;Manzano-Sánchez and Valero-Valenzuela, 2018). Nor is the phenomenon confined to teenagers: Czajka et al (2015) have observed a similar trend in childhood, which they attribute to the influence of the children's parents.…”
Section: Discussionmentioning
confidence: 78%
“…Results from other studies also highlight significant quantitative variability between weekday and weekend PA among adolescents (Pelclová et al, 2010;Manzano-Sánchez and Valero-Valenzuela, 2018). Nor is the phenomenon confined to teenagers: Czajka et al (2015) have observed a similar trend in childhood, which they attribute to the influence of the children's parents.…”
Section: Discussionmentioning
confidence: 78%
“…According to gender, it seems that there are differences between boys and girls, with higher values of MVPA in boys, regardless of whether they are measured during the week or on weekends ( Aibar et al, 2014 ). Other studies have not identified differences according to gender in teenagers ( Manzano-Sánchez and Valero-Valenzuela, 2018 ) or children ( Svedenkrans et al, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…One of the main purposes of PE classes is to improve some variables to increase the adherence to PA in children and teenagers. Some studies that have used model-based learning can improve motivation, autonomy and competence, and these variables have a significant relation with MVPA ( Manzano-Sánchez and Valero-Valenzuela, 2018 ). Recently, the Teaching Personal and Social Responsibility (TPSR) model has demonstrated improvements in these variables ( Martínez-Vizcaíno and Sánchez-López, 2008 ; Manzano-Sánchez and Valero-Valenzuela, 2019 ; Manzano-Sánchez et al, 2019 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of this study was that there was a scarce sample in a very wide sample universe, since the use of accelerometry caused that some of the participants had to be excluded because they did not meet the inclusion criteria, as it happened in other studies such as Manzano-Sánchez and Valero-Valenzuela (2018). On the other hand, the scale of competence had a low reliability value.…”
Section: Discussionmentioning
confidence: 92%